Increased Age and Long Working Period Associated with Increased Severi-ty of Pterygium Among Fishermen in Kedung Cowek Sub-District, Surabaya, East Java-Indonesia - Irma Andriani Pasaribu; Prawesty Diah Utami (Indonesian Journal of Medical Sciences and Public Health, 2021)
Pterygium is a degenerative and invasive disorder of the subconjunctival tissue that can reach the cornea area which is become a worldwide health problem. UV exposure is the biggest risk factor for pterygium. A profession as a fisherman is one of the occupations that are often related to the appearance of pterygium, because of long-term exposure to UV rays. This study aimed to determine the correlation between age and duration as a fisherman with the degree of pterygium in Kedung Cowek village, Bulak Surabaya district, East Java - Indonesia. The research design was an analytic observational using consecutive sampling during March - July 2011; with the total number of respondents is 42 fishermen who met the inclusion criteria. The results of the statistical analysis test showed that there was a strong and significant relationship between the age of the fishermen (p = 0.007; coefficient correlation = 502) and the duration of working as a fisherman (p = 0.029; coefficient correlation = 409) with the severity of the pterygium. Based on these results it can be concluded that the age and duration of work as fishermen are related to the severity of the pterygium in fishermen in the Kedung Cowek sub-district, Surabaya, East Java-Indonesia.